2019
DOI: 10.1007/s40268-019-0266-z
|View full text |Cite
|
Sign up to set email alerts
|

Multikinase Abl/DDR/Src Inhibition Produces Optimal Effects for Tyrosine Kinase Inhibition in Neurodegeneration

Abstract: Background and objectives Inhibition of Abelson (Abl) tyrosine kinase as a therapeutic target has been gaining attention in neurodegeneration. Post-mortem Alzheimer’s and Parkinson’s disease brains show that the levels of several other tyrosine kinases, including Discoidin Domain Receptors (DDR1/2) are elevated. Knockdown of these tyrosine kinases with shRNA reduces neurotoxic proteins, including alpha-synuclein, beta-amyloid and tau. Methods Direct profiling of the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
62
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 81 publications
9
62
0
Order By: Relevance
“…[4][5][6] However, nilotinib more potently inhibits DDR1 (IC 50 = 1-8 nM). [4][5][6][7][8] The concentration of CSF nilotinib in 150 mg and 300 mg nilotinib-treated groups (3.46 nM and 4.7 nM, respectively) exceeds the IC 50 required to inhibit DDR1. Therefore, nilotinib achieves sufficient CSF levels to what would potentially inhibit DDR1, and alter disease biomarkers.…”
Section: July 2020 191mentioning
confidence: 97%
See 2 more Smart Citations
“…[4][5][6] However, nilotinib more potently inhibits DDR1 (IC 50 = 1-8 nM). [4][5][6][7][8] The concentration of CSF nilotinib in 150 mg and 300 mg nilotinib-treated groups (3.46 nM and 4.7 nM, respectively) exceeds the IC 50 required to inhibit DDR1. Therefore, nilotinib achieves sufficient CSF levels to what would potentially inhibit DDR1, and alter disease biomarkers.…”
Section: July 2020 191mentioning
confidence: 97%
“…3 Nilotinib (Tasigna, AMN107; Novartis, Switzerland) is a tyrosine kinase inhibitor that preferentially targets discoidin domain receptors (DDRs) [4][5][6][7][8] and effectively reduces misfolded proteins in animal models of neurodegeneration. 7,[9][10][11][12][13][14][15][16] Nilotinib also targets the nonreceptor tyrosine kinase Abelson [4][5][6] and is FDAapproved for the treatment of Philadelphia chromosome positive chronic myeloid leukemia (CML) at oral doses of 300 mg twice daily. [4][5][6] Low doses of nilotinib penetrate the bloodbrain barrier and promote the degradation of Aβ and tau in animal models of neurodegeneration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is the prototype of a larger family, comprising at least nine members, most of them with little activity in normal cells in the absence of stimulatory signals (2). Src kinases have been suggested to be involved in the exacerbation of neurodegenerative pathologies, whereas their inhibition would diminish microgliosis and mitigate inflammation, findings that are in line with experimental effects seen for non-specific src inhibitors such as bosutinib or LCB-03-0110 (3). Inhibition of src kinases has been suggested by non-clinical evidence as a potential method of therapy for the pulmonary vascular remodeling and right ventricular hypertrophy in pulmonary hypertension (4), although several reports indicate that dual Abl/src inhibitor dasatinib may actually induce pulmonary hypertension (5)(6)(7); it was more recently suggested that this dasatinib effect may in fact be independent of the src inhibition (7).…”
Section: Introductionmentioning
confidence: 70%
“…Recent evidence suggests the involvement of c-Abl TK in the pathogenesis of PD through Parkin inactivation, a-synuclein aggregation, and impaired autophagy of toxic elements [7]. Inhibition of this kinase activity has been suggested as a potential target in the treatment of PD [7,8]. Indeed, Suresh and colleagues [5] found that PD180970 clears toxic protein aggregates and exerts cytoprotection against a-synuclein toxicity in an autophagy-dependent manner through increased autophagy flux and augmented autophagosome numbers in vitro.…”
mentioning
confidence: 99%